The Role of Implementing Adolescent Posyandu on Adolescent Reproductive Health Behavior: Scoping Review - Devita Vida A'yun; Nafira Zenina; Shufi Arofiqandil; Niken Bayu Argaheni (Borneo Scientific Publishing, 2023)
Adolescence is a transitional stage filled with biopsychosocial and environmental challenges. Teenagers often face difficulties in managing these challenges, which may lead to health issues, including risky sexual behavior driven by curiosity or desire, involving either the opposite or same sex. The rising incidence of adolescent health problems underscores the need for equitable and integrated interventions that support clean and healthy lifestyles, as well as strong social and life skills. One approach is the establishment of adolescent-friendly health services, such as integrated service posts (Posyandu Remaja), which serve as platforms for health education, counseling, and reproductive health services tailored to adolescent needs.This study aims to map existing evidence on the role of adolescent health services in shaping reproductive health behavior. A scoping review was conducted using national journal databases, Google Scholar, and ResearchGate, focusing on full-text Indonesian-language articles from 2018 to 2023. Five relevant studies were identified, covering various regions and research designs. The findings show that adolescents who actively participate in Posyandu Remaja tend to exhibit better reproductive health behavior. This suggests that adolescent health services play a key role in promoting healthy reproductive choices. Strengthening these services is essential to support adolescent well-being and development.